ETNOBOTANI MASYARAKAT SUKU DAYAK KERABAT DI DESA TAPANG PERODAH KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Kuni, Bitenia Elen; Hardiansyah, Gusti; Idham, M. (Universitas Tanjungpura, 2015)
Ethnobotany is the study of a direct relationship between human and plant in traditional utilization. Ethnobotany is oneamong theway to preserve thetraditions in used plants. The purpose of this research is to identifyandobtainknowledge in used plant by Dayak Kerabat ethnic in Tapang Perodah Village regency of Sekadau subdistrict Sekadau Hulu in their daily live. The method is used to determine of the respondent is purposive sampling with the number of informan is 40. Analysis the data is used approachment descriptive analysis with kualitative approach, the data have been gotten from interview guide were analized with saw the answers from the informant. There have 185 species of plant consist of 70 family ang 9 groups is used that covered 115 species food plant, 14 food livestock, 52 species medicinal plants, 13 species building’ material plant, 11 species firewood, 9 species webbing rope and handicraft, poison is 1 species, 25 species ornamental plant and 9 species traditionalplant. The plant is used by dayak kerabat ethnic giveeffect to thedaily needs in tapang perodah village, this isa verypreciousknowledge that need to dig upandconserved so this knowledge is not disappearingalong with development of the period. Rareplant species diversity need to develop so thatits preservationalways protected and needfurther research to know the potentialofsome useful plants utilized by Dayak Kerabat ethnic. Keywords : Dayak Kerabat Ethnic, Ethnobotany,VillageTapangPerodah